2021
DOI: 10.3389/feduc.2021.714526
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Towards and Adoption of the Novel Learning Environment Among Undergraduate Medical Students During COVID-19

Abstract: Higher education has changed significantly since the beginning of the COVID-19 pandemic. Medical education programs with extensive practical and interactive components faced major challenges to protect students, faculty and patients. In response to COVID-19, many medical schools worldwide shut down undergraduate medical education and converted most of their teaching to digital formats. The aim of this paper is to assess the attitude towards and adoption of the novel learning environment among undergraduate med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(41 reference statements)
2
2
0
Order By: Relevance
“…According to our qualitative data, the lack of direct contact with fellow students, which could only take place via online media, affects both student professions negatively. These findings complement a recent empirical study in which undergraduate medical students reported lack of interactions with peers, faculty and patients in practice as negative aspects of digital teaching 44. For dental students, the lack of practical training played a major role, as dentists usually take dental courses from the first semester onwards to learn the practical skills from early stage on 45.…”
Section: Discussionsupporting
confidence: 79%
“…According to our qualitative data, the lack of direct contact with fellow students, which could only take place via online media, affects both student professions negatively. These findings complement a recent empirical study in which undergraduate medical students reported lack of interactions with peers, faculty and patients in practice as negative aspects of digital teaching 44. For dental students, the lack of practical training played a major role, as dentists usually take dental courses from the first semester onwards to learn the practical skills from early stage on 45.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, our qualitative results mapped several scales of the Medical School Learning Environment Survey: among others, but not limited to “flexibility,” “student–student interaction,” “meaningful learning experience,” and “nurturance” ( Rusticus et al, 2014 ). In line with recent studies, perception of the changed situation of the students included both negative and positive aspects ( Elmer et al, 2020 ; Mohr et al, 2021 ). In this study, the flexibility due to digital teaching with few real-time courses is particularly noteworthy.…”
Section: Discussionsupporting
confidence: 80%
“…In their study, Mohr et al showed that female students and first-year students in particular were more comfortable with digital teaching. Students with childcare and job obligations also benefited from this mode of studying [57]. However, for data protection reasons, in our study.…”
Section: Discussionmentioning
confidence: 70%
“…Students who work or have to care for children may also have participated less frequently due to time constraints. Also, considering the study of Mohr et al [57], the preference for (asynchronous and therefore more flexible) digital teaching offers could possibly be underestimated.…”
Section: Discussionmentioning
confidence: 99%